2015
DOI: 10.1111/jpi.12258
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the mechanism of melatonin impacts on maize seedling growth: sugar metabolism as a case

Abstract: Melatonin regulates growth in many plants; however, the mechanism remains unclear. In this study, exogenous melatonin feeding resulted in both promotional (≤10 μm) and inhibitory (≥100 μm) effects on maize seedling growth. Initial analyses suggested positive correlations between the amount of melatonin and sucrose synthesis and hydrolysis-related gene expression, enzyme activities, and sucrose metabolites. However, assays of photosynthetic rate, hexokinase (HxK) activity, expression of photosynthetic marker ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 73 publications
13
89
0
Order By: Relevance
“…The interaction with the cytokinin or 5HT responses may also be a causal factor. A recent study on Zea mays has also suggested a direct interaction with sugar metabolism 101 . This publication reported that at low levels (10 µM) MEL acted to enhance gene expression of photosynthesis, sucrose biosynthesis and hydrolysis-related genes, to increase starch catabolism during the night, to elevate sucrose-related enzyme activity and to promote photosynthetic rates.…”
Section: Melatonin and Shoot Organogensismentioning
confidence: 98%
See 2 more Smart Citations
“…The interaction with the cytokinin or 5HT responses may also be a causal factor. A recent study on Zea mays has also suggested a direct interaction with sugar metabolism 101 . This publication reported that at low levels (10 µM) MEL acted to enhance gene expression of photosynthesis, sucrose biosynthesis and hydrolysis-related genes, to increase starch catabolism during the night, to elevate sucrose-related enzyme activity and to promote photosynthetic rates.…”
Section: Melatonin and Shoot Organogensismentioning
confidence: 98%
“…This publication reported that at low levels (10 µM) MEL acted to enhance gene expression of photosynthesis, sucrose biosynthesis and hydrolysis-related genes, to increase starch catabolism during the night, to elevate sucrose-related enzyme activity and to promote photosynthetic rates. This was coupled to a rise in the expression of sugar transporters SUT1 and SUT2 as well as higher levels of hexokinase activity and sugar metabolites which resulted in elevated levels of available sugars for plant growth 101 . Interestingly, when the authors increased exogenously applied MEL concentrations to 100 µM, the reverse effect was seen with reduced sucrose metabolism, transport and gene expression, increased starch accumulation in photosynthesizing tissues and lower photosynthetic rates 101 .…”
Section: Melatonin and Shoot Organogensismentioning
confidence: 99%
See 1 more Smart Citation
“…Sucrose influences and reflects photosynthesis, C export, and nutrient mobilization (Figure 1). Sucrose is the primary product of photosynthesis, the form in which carbohydrates are transported from the photosynthetic tissues (i.e., the source) to non-photosynthetic tissues (i.e., the sink) and the initial building block of most natural organic matter [10]. In the photosynthetic tissues, sucrose is synthesized by the enzyme sucrose phosphate synthase (SPS) via the consumption of uridine diphosphate glucose (UDP-G) from the Calvin cycle and fructose-6-phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…80 Reports, which investigated effect of exogenous melatonin on both tomato's and maize's seeds, have confirmed this case too. 78,81 Melatonin plays an important role to maintain the vitality of the plants. 82 KOCA ÇALIŞKAN et al Plant's Melatonin …”
Section: Functions Of Phytomelatoninmentioning
confidence: 99%